The right of disabled people to consultation: Curriculum development in social education - Löve, Laufey Elísabet (Menntavísindasvið Háskóla Íslands, 2024)
The research this article draws on examines the right of disabled people to participate in decision-making in matters that affect their interests in line with the UN Convention on the Rights of Persons with Disabilities (CRPD). Recognising the need to interpret this right broadly, as called for by the Committee on the Convention, this research focuses on participation in curriculum development in the field of social education at the University of Iceland. As licensed professionals, social educators provide key services and supports for disabled people’s right to full and effective participation at all levels of society. Disabled people, therefore, have a vested interest in the education of social educators. Their experiences and views must be heard and included in the curriculum development. This research focuses on consultations with people with intellectual disabilities, recognising that as a group, they often depend on the services and supports provided by social educators but have often had limited opportunity to express their views and concerns in decision-making processes. The theoretical foundation of this research is rooted in the human rights approach to disability, which focuses, first and foremost, on disabled people as rights-holders. States and state actors are responsible for ensuring and upholding these rights. Failure to do so is considered a breach of disabled people’s human rights. The human rights approach is closely related to the CRPD, which it both supports and reflects, including its emphasis on the rights of disabled people to take part in decision-making in matters that affect their lives. The objective of this research was three-fold: first, to support the rights of disabled people to have a say in matters that concern their interests and affairs, in line with the CRPD; second, to improve the curriculum of a first-year course in the study of social education by drawing on the knowledge and lived experience of people with intellectual disabilities as experts in their own lives; and, ...